British laypeople’s attitudes towards gradual sedation, sedation to unconsciousness and euthanasia at the end of life - Takla, A; Savulescu, J; Kappes, A; Wilkinson, D (Public Library of Science, 2021)
Background Many patients at the end of life require analgesia to relieve pain. Additionally, up to 1/5 of patients in the UK receive sedation for refractory symptoms at the end of life. The use of sedation in end-of-life care (EOLC) remains controversial. While gradual sedation to alleviate intractable suffering is generally accepted, there is more opposition towards deliberate and rapid sedation to unconsciousness (so-called “terminal anaesthesia”, TA). However, the general public’s views about sedation in EOLC are not known. We sought to investigate the general public’s views to inform policy and practice in the UK. Methods We performed two anonymous online surveys of members of the UK public, sampled to be representative for key demographic characteristics (n=509). Participants were given a scenario of a hypothetical terminally ill patient with one week of life left. We sought views on the acceptability of providing titrated analgesia, gradual sedation, terminal anaesthesia, and euthanasia. We asked participants about the intentions of doctors, what risks of sedation would be acceptable, and the equivalence of terminal anaesthesia and euthanasia. Findings Of the 509 total participants, 84% and 72% indicated that it is permissible to offer titrated analgesia and gradual sedation (respectively); 75% believed it is ethical to offer TA. Eighty-eight percent of participants indicated that they would like to have the option of TA available in their EOLC (compared with 79% for euthanasia); 64% indicated that they would potentially wish for TA at the end of life (52% for euthanasia). Two-thirds indicated that doctors should be allowed to make a dying patient completely unconscious. More than 50% of participants believed that TA and euthanasia were non-equivalent; a third believed they were. Interpretation